Quantitative changes in the oral microflora of patients fed by transnasal tubes - Chávarri Vásquez, Maira Alejandra (2014)
Objective: To determine differences in the growth of oral microflora in patients fed through transnasal probe compared to patients with oral feeding, was the objective of this study. Methodology: it were selected 15 patients having transnasal probe feeding (study group), and 15 patients with oral feeding (control group), both groups from the internal medicine and surgery services at the National Hospital Dos de Mayo, Lima-Peru, who met the inclusion criteria to be considered in the sample. It was done an assessment of microbiological growth in selective media for streptococci and Candida albicans, from samples of the buccal sulcus of the oral cavity, taken by swabbing the selected patients. Results: Growth assessment was performed and statistical analysis using chi square test with a significance level of p <0.05 for streptococci and p <0.005 for candida albicans. Conclusions: There is an increased growth of streptococci and Candida albicans in patients fed through transnasal probe compared to patients with oral feeding.